The Effect of Work Discipline and Work Motivation on Employee Performance at UPT Puskesmas Ambalawi District - muhammad iqbal; Airulmukminin Airulmukminin (Fakultas Ekonomi Universitas Indonesia Timur, 2020)
Performance is a very important factor for a government agency or other organization. Performance as a manifestation of one's work behavior is displayed as work performance in accordance with its role within the organization for a certain period of time. Performance can be seen from the Work Discipline and Work Motivation of its employees. This research was conducted to see whether there was an effect of work discipline and work motivation on employee performance at the UPT Puskesmas Ambalawi District, Bima Regency. This type of research used in this study is asositive, the number of respondents determined from 127 populations is equal to 55 respondents with random sampling techniques. The research instrument uses a Likert scale questionnaire, data collection techniques used are observation, interviews, questionnaires and literature studies, using data analysis techniques validity, reliability, classic assumption test, multiple regression analysis, multiple correlation analysis, determination test, T test and Test F. After the instrument is declared valid and reliable, the results of data analysis using the SPSS application are obtained, the data is normally distributed, multicollinearity does not occur, and autocorrelation. So that continued data analysis, obtained a correlation level of 65.6% while a coefficient of determination of 43%. The analysis results partially show that Work Discipline influences Employee Performance While Work motivation does not affect employee Performance. Simultaneously work discipline and work motivation affect employee performance at UPT Puskesmas Ambalawi District, Bima Regency. Keywords: Work discipline, employee performance, work motivation